Association of health literacy with short-term postoperative outcomes in older adult patients with abdominal tumors undergoing surgery and perioperative rehabilitation program: A prospective cohort study. Issue 2 (March 2023) - Iwakura, Masahiro; Kawagoshi, Atsuyoshi; Furukawa, Yutaka; Sugawara, Keiyu; Wakabayashi, Toshiki; Sato, Tsutomu; Wakasa, Masahiko
Abstract: Introduction: Low health literacy (HL) is associated with poor surgical outcomes in patients with abdominal tumors, despite enhanced recovery programs. However, the relationship between HL and postoperative outcomes, including health-related quality of life (HRQOL) and physical functions, has been unclear in patients with abdominal tumors receiving perioperative rehabilitation programs (PRPs). Our objective was to identify associations of HL with postoperative functional and general outcomes in patients with abdominal tumors undergoing surgery and PRPs, controlling for critical covariates. Materials and Methods: The prospective cohort study was conducted from April 2020 to December 2021 in a single acute care hospital in Akita City, Japan. Out of 112 consecutive older adults with abdominal tumors referred to PRPs before surgery for tumors, 101 participated. Three patients declined undergoing follow-up assessment, and thus 97 were analyzed. Demographic data, comorbidities, education, surgical procedure, frailty status, cognitive functions, physical activity, nutritional status, tumor sites, types, and stages were collected as covariates at baseline. All participants underwent PRPs. HL was measured using the Japanese version of the European Health Literacy Survey Questionnaire, a comprehensive HL measurement. Primary endpoints were changes in HRQOL, measured using the EuroQol 5-dimension 5-level (EQ-5D-5L) index and EuroQol-visual analog scale (EQ-VAS), and physical functions (chair-stand ability, usual gait speed, and grip strength) from before surgery to discharge. Secondary endpoints were 90-day readmissions, postoperative complications, and length of hospital stay. Multivariate regression with inverse probability weighting, using propensity scores, estimeted associations of HL with the outcomes. Results: Of the 97 patients (36 [37.1%] women, mean [standard deviation] age 74.4 [6.3] years), 42 (43.3%) reported low HL. At baseline, patients with low HL exhibited worse EQ-5D-5L scores ( P = .001), EQ-VAS values ( P = .03), chair-stand ability ( P = .001), and gait speed ( P = .03) than controls. Low HL was associated with a low risk of grip strength declines (risk ratio, 0.13; 95% confidence interval, 0.12–0.99) but not with any other outcome. Discussion: There appeared to be no apparent associations of HL with surgical outcomes in patients with abdominal tumors receiving PRPs. Thus, HL might not be a crucial predictor of surgical outcomes when combined with PRPs.